(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study aimed to identify the Arabic handwriting skills required for upper elementary school students. The study adopted the descriptive-analytical approach, and its population consisted of faculty members specialized in Arabic language curricula and instruction at Saudi universities. The researchers selected a representative random sample of ten (10) academics from various Saudi universities. A list was prepared that included the Arabic handwriting skills needed for upper elementary school students. The study concluded by identifying these essential handwriting skills. In light of this, the study recommends training students in Arabic handwriting skills and assessing them within the My Beautiful Language curriculum, as well as enhancing opportunities for applying handwriting skills with a focus on learning efficiency.